2018
DOI: 10.12659/msmbr.911786
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Processes in Mind-Body Medicine: Chronic Stress, Cell Aging, and Telomere Length

Abstract: Stress affects cellular aging and inflammatory and chromosomal processes, including telomere length, thereby potentially compromising health and facilitating disease onset and progression. Stress-related diseases and strategies to manage stress usually require integrative or behavioral therapeutic approaches that also operate on cellular levels. Mind-body medicine (MBM) uses the interaction between the mind, body, behavior, and the environment to correct physical and psychological malfunctions, thus ameliorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
(62 reference statements)
2
25
0
2
Order By: Relevance
“…During stress, changes in gut microbes could affect the regulation of neurotransmitters mediated by microbes and gut function; [ 39 ] meanwhile, traditional Chinese exercise uses the interaction between thought, body, behavior, and environment to correct the body and mental dysfunction, contributing to better physical and mental health. [ 40 ] Another finding of this study may provide a scientific idea, and different intervention methods focus on different emotional problems. This conclusion may be controversial due to the limitations of the articles included in this study (such as the quality of the included articles) while this may also provide a new idea for future research.…”
Section: Discussionmentioning
confidence: 95%
“…During stress, changes in gut microbes could affect the regulation of neurotransmitters mediated by microbes and gut function; [ 39 ] meanwhile, traditional Chinese exercise uses the interaction between thought, body, behavior, and environment to correct the body and mental dysfunction, contributing to better physical and mental health. [ 40 ] Another finding of this study may provide a scientific idea, and different intervention methods focus on different emotional problems. This conclusion may be controversial due to the limitations of the articles included in this study (such as the quality of the included articles) while this may also provide a new idea for future research.…”
Section: Discussionmentioning
confidence: 95%
“…A randomized study showed that MBSR may be a novel treatment approach for reducing social risk factors like loneliness as well as like molecular pro-inflammatory gene expression in older adults (83). In general, meditation seem to have a potential for inflammation reduction, including gene expression, cellular and chromosomal health (84). This also includes self-regulation and self-healing capacities, i.e., the innate restorative capacities of mind and body (64).…”
Section: Mind-body Medicine (Mbm)mentioning
confidence: 99%
“…Most authors have shown that short telomeres are associated with an increased risk of MI, CHD, atherosclerosis and other pathologies [ 39 , 41 , 52 ]. At the same time, many scientists showed an association of short telomeres with diseases, which are not connected with cardiovascular system, such as male and female sterility [ 44 ], obesity [ 54 ], stress [ 55 ], different oncological [ 56 ] and psychical diseases [ 57 ]. For the same nosologies, hyperproduction of reactive oxygen species was shown, i.e.…”
Section: Discussionmentioning
confidence: 99%